Integrating science for water security governance - Kristen M. Whitney; Rebecca M. Peters; Anil Mishra; Annalise G. Blum; Perry C. Oddo; Kate A. Brauman; Angelica L. Gutierrez; John D. Bolten; Matthew J. McCarthy; Andrés Sánchez (Global Environmental Change, 2026)

Equine neorickettsiosis: A global perspective of the natural habitat of the bacteria and clinical disease - Luis G. Arroyo; Alexandre S. Borges; John D. Baird; Brian D. Perry; Yasuko Rikihisa; Stephen E. Greiman (Veterinary Microbiology, 2026)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Coral carbonate production across depth: homogenisation after bleaching? - Sivajyodee Sannassy Pilly; Ronan C. Roche; Ines D. Lange; Chris T. Perry; Andrew O. M. Mogg; Kathryn Dawson; John R. Turner (Coral Reefs, 2024)
Recurrent climate-driven warming events, which can induce severe coral bleaching and mortality on tropical reefs, are predicted to cause homogenisation of coral communities and loss of ecosystem functions in shallow reef systems (< 30 m). However, data documenting the variation in coral carbonate production across depth are limited. Here we explore differences in coral cover, community composition, coral colony size structure and carbonate production rates between two depths (10 m and 17.5 m) across four atolls in the remote Chagos Archipelago. We show higher coral carbonate production rates at 10 m (4.82 ± 0.27 G, where G = kg CaCO 3 m −2 yr −1 ) compared to sites at 17.5 m (3.1 ± 0.18 G). The main carbonate producers at 10 m consisted of fast-growing branching and tabular corals (mainly Acroporids) and massive corals (mainly Porites ), with high abundances of medium- and large-sized colonies. In contrast, coral carbonate production at 17.5 m was driven by slow-growing encrusting and foliose morphotypes and small colony sizes. Utilising a dataset following 6–7 years of recovery after the 2015–2017 bleaching event, our results show that depth-homogenisation of coral communities was temporary and carbonate production rates at 10 m depth recovered quicker at 3 of 4 studied atolls. The exception is Great Chagos Bank where slower recovery of branching and tabular corals at 10 m has led to a longer-lasting depth-homogenisation of carbonate production rates. The latter example cautions that more frequent bleaching events may drive increasing homogenisation of carbonate production rates across depth gradients, with implications for vital reef geo-ecological functions.

Phylogenomic analyses of multidrug resistant Corynebacterium striatum strains isolated from patients in a tertiary care hospital in the UK - Vartul Sangal; Emma C. L. Marrs; Andrew Nelson; John D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Corynebacterium striatum is an emerging nosocomial pathogen. This is the first report showing the presence of three distinct multidrug resistant lineages of C. striatum among patients in a UK hospital. The presence of ErmX, Tet(W), Bla and AmpC proteins, and mutations in gyrA gene are associated with the resistance to clindamycin, doxycycline, penicillin and moxifloxacin, respectively. These strains are equipped with several corynebacterial virulence genes including two SpaDEF-type and a novel pilus gene cluster, which needs further molecular characterisation. This study highlights a need of developing an active surveillance strategy for routine monitoring and preventing potential cross-transmission among susceptible patients.

A cloudy forecast for species distribution models: Predictive uncertainties abound for California birds after a century of climate and land‐use change - John D. J. Clare; Perry de Valpine; Diana A. Moanga; Morgan W. Tingley; Steven R. Beissinger (Global Change Biology, 2024)
Correlative species distribution models are widely used to quantify past shifts in ranges or communities, and to predict future outcomes under ongoing global change. Practitioners confront a wide range of potentially plausible models for ecological dynamics, but most specific applications only consider a narrow set. Here, we clarify that certain model structures can embed restrictive assumptions about key sources of forecast uncertainty into an analysis. To evaluate forecast uncertainties and our ability to explain community change, we fit and compared 39 candidate multi‐ or joint species occupancy models to avian incidence data collected at 320 sites across California during the early 20th century and resurveyed a century later. We found massive (>20,000 LOOIC) differences in within‐time information criterion across models. Poorer fitting models omitting multivariate random effects predicted less variation in species richness changes and smaller contemporary communities, with considerable variation in predicted spatial patterns in richness changes across models. The top models suggested avian environmental associations changed across time, contemporary avian occupancy was influenced by previous site‐specific occupancy states, and that both latent site variables and species associations with these variables also varied over time. Collectively, our results recapitulate that simplified model assumptions not only impact predictive fit but may mask important sources of forecast uncertainty and mischaracterize the current state of system understanding when seeking to describe or project community responses to global change. We recommend that researchers seeking to make long‐term forecasts prioritize characterizing forecast uncertainty over seeking to present a single best guess. To do so reliably, we urge practitioners to employ models capable of characterizing the key sources of forecast uncertainty, where predictors, parameters and random effects may vary over time or further interact with previous occurrence states.

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Importance of Biogeomorphic and Spatial Properties in Assessing a Tidal Salt Marsh Vulnerability to Sea-level Rise - Karen M. Thorne; Deborah L. Elliott-Fisk; Glenn D. Wylie; William M. Perry; John Y. Takekawa (Estuaries and Coasts, 2014)

Determining the influence of environmental and patient specific factors on the polymicrobial communities of the cystic fibrosis airway - Andrew Nelson; Audrey Perry; John D. Perry; Stephen J. Bourke; Stephen P. Cummings; Anthony De Soyza (Antonie van Leeuwenhoek, 2013)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Assessing Potential Risk to Alligators, Alligator mississippiensis, from Nutria Control with Zinc Phosphide Rodenticide Baits - Gary W. Witmer; John D. Eisemann; Thomas M. Primus; Jeanette R. O’Hare; Kelly R. Perry; Ruth M. Elsey; Phillip L. Trosclair (Bulletin of Environmental Contamination and Toxicology, 2010)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

The effects of cannabinoids on serum cortisol and prolactin in humans - Mohini Ranganathan; Gabriel Braley; Brian Pittman; Thomas Cooper; Edward Perry; John Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2009)

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine - Hyun-Sang Cho; Deepak C. D’Souza; Ralitza Gueorguieva; Edward B. Perry; Steven Madonick; Laurence P. Karper; Anissa Abi-Dargham; Aysenil Belger; Walid Abi-Saab; Deborah Lipschitz; Alexandre Bennet; John P. Seibyl; et al. (Psychopharmacology, 2005)

Preliminary evidence of attenuation of the disruptive effects of the NMDA glutamate receptor antagonist, ketamine, on working memory by pretreatment with the group II metabotropic glutamate receptor agonist, LY354740, in healthy human subjects - John H. Krystal; Walid Abi-Saab; Edward Perry; D. Cyril D’Souza; Nianjin Liu; Ralitza Gueorguieva; Lisa McDougall; Tracy Hunsberger; Aysenil Belger; Louise Levine; Alan Breier (Psychopharmacology, 2005)

NMDA receptor antagonist effects, cortical glutamatergic function, and schizophrenia: toward a paradigm shift in medication development - John H. Krystal; D. Cyril D'Souza; Daniel Mathalon; Edward Perry; Aysenil Belger; Ralph Hoffman (Psychopharmacology, 2003)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)